Gendered Violence in Biblical Narrative The Devouring Metaphor - Brownsmith, Esther (Oxford Taylor & Francis Group, 2024)
This book uses three examples of violent biblical stories about women, explored through the lens of conceptual metaphor theory in relation to culinary language used within these texts, to examine wider issues of gender and sexual violence in the Hebrew Bible.
Cover -- Half Title -- Series -- Title -- Copyright -- Table of Contents -- List of Figures -- Acknowledgments -- 1 Amuse-Bouche -- (a) Like a Bone to Dogs -- (b) Overview of Chapters -- 2 Stocking the Pantry -- (a) Metaphor in Narrative -- (b) Realized Metaphors -- (c) Woman as Food: A Cross-cultural History -- (d) "Woman is food" in the Bible and the Ancient Near East -- (e) What Conclusions Can Be Drawn? -- 3 The Woman in the Refrigerator: Consumption and Objectification in Judges 19 -- (a) Preliminary Considerations -- (b) Tizkoret as Absent Referent -- (c) Objectification -- (d) Dismemberment -- (e) Consumption -- (f) The Invisible Woman -- 4 Forbidden Fruit: Food and/as Consumption in 2 Samuel 13 -- (a) Nibbling at the Text -- (b) "Lusty Latkes"? Interrogating the לְבִבוֹת -- (c) My Sister, My Bride: Intertextual Links with Song of Songs 4 -- (d) Raw, Cooked, and Rotten: The Cycle of Consumption in 2 Samuel 13 -- 5 The Diner as Dinner: Jezebel and the Literalization of Metaphor -- (a) Enter Jezebel -- (b) Jezebel in Her Prime -- (c) Airbrushing the Meal: Appearance, Objectification, and Jezebel's Death -- (d) Pruning the Vineyard in Metaphor and Reality -- (e) Anat and Jezebel: Parallels and Divergences -- (f) Jezebel: Conclusions and Insights from Blending -- 6 Clearing the Table -- (a) Reevaluating the Case Studies -- (b) The Future of the Realized Metaphor -- (c) Dead Metaphors, Living Women -- Bibliography -- Indexes.
Description based on publisher supplied metadata and other sources
Keywords: Bibel; Geschlecht; Gewalt; Hermeneutik; Hochschulschrift